COVID-19 and the heart. Issue 1 (24th September 2022) - Roy, Roman; McDonaugh, Benedict; O'Gallagher, Kevin
Abstract: Background: There is evidence for a bi-directional relationship between COVID-19 and the cardiovascular (CV) system. Source of data: Published literature. Areas of agreement: Pre-existing heart failure (HF) increases the risk of mortality with COVID-19. CV complications are recognized, including increased rates of acute coronary syndromes, HF, arrhythmia and myocarditis. Drugs targeting the angiotensin system are safe and may provide prognostic benefit. Areas of controversy: Vaccination as a cause of myocarditis remains a key area of contention. Growing points: As the pandemic progresses, we are gaining more data about the long-term effects of COVID-19 on the CV system: long COVID, and medium-to-long-term increases in CV risk. Areas timely for developing research: Large-scale longitudinal studies will shed light on long-term CV outcomes with COVID-19. Furthermore, the differential effects of COVID-19 variants on the CV system must be investigated.